The College Students’ Sense of Responsibility for Innovation and Entrepreneurship - Zhang, Qing; Liu, Congchong; Wang, Zehao; Yang, Zimo (Frontiers in Psychology, 2020)
The purpose of this paper is to analyze the relationship between positive psychological quality and college students’ sense of responsibility for innovation and entrepreneurship from the perspective of positive psychology, explore the cultivation model that can effectively improve college students’ sense of responsibility for innovation and entrepreneurship, and promote their success in entrepreneurship. In this study, a total of 1,500 college students were selected for questionnaire survey. ANOVA was used to analyze the differences of innovation and entrepreneurship responsibilities in demographic variables; factor analysis models were used to explore the factors that influence college students’ sense of responsibility for innovation and entrepreneurship; and Spearsman correlation and linear regression were used to analyze the relationship between college students’ positive quality and innovation and entrepreneurship. The results showed that the average scores of individual responsibility, team responsibility and social responsibility were 3.290, 3.624 and 3.720, respectively; individual responsibility differed significantly at the grade level; group responsibilities and social responsibilities were significantly different at the grade and gender levels; the linear fitting between benevolence, super-excellence, bravery, restraint, and wisdom with team responsibilities all reached significant levels, among which the wisdom coefficient was the highest; the linear fitting between syngroup, excellence, bravery, modesty and wisdom with social responsibility reached a significant level, among which the wisdom coefficient was the highest; the linear fitting between syngroup, excellence, bravery, modesty and wisdom with personal responsibility reached a significant level, among which the coefficient of excellence was the highest. This indicated that positive psychological qualities such as syngroup, excellence, modesty, benevolence, super-excellence, bravery, restraint, and wisdom were the influencing factors of college students’ sense of responsibility for innovation and entrepreneurship. Among them, the role of wisdom is the most noteworthy in predicting social and group responsibilities, and super-excellent is the most significant predictor for individual responsibility.